Scaling Agile - Ebert, Christof; Paasivaara, Maria (IEEE software, 2017)
Agile software development has become mainstream. Industry-scale agility for distributed teams, large projects, or critical systems requires scaling agile practices, which agile scaling frameworks attempt to provide. Here, Maria Paasivaara and I explore frameworks such as the Scaled Agile Framework (SAFe) and show best practices from two industry case studies. I look forward to hearing from both readers and prospective column authors about this column and the technologies you want to know more about.